Health-related quality of life and functionality in primary caregiver of surviving pediatric COVID-19 - Martins, Fernanda; Gonçalves, Fernanda T.; Imamura, Marta; Barboza, Daniela S.; Matheus, Denise; Pereira, Maria Fernanda B.; Marques, Heloisa H. S.; Correa-Silva, Simone; Montenegro, Marilia M.; Fink, Thais T.; Lindoso, Livia; Bain, Vera; et al. (Frontiers in Public Health, 2023)
OBJECTIVES: To prospectively assess health-related quality of life (HRQoL), global functionality, and disability in primary caregivers of surviving children and adolescents after COVID-19. METHODS: A longitudinal observational study was carried out on primary caregivers of surviving pediatric post-COVID-19 patients (n=51) and subjects without COVID-19 (n=60). EuroQol five-dimension five-level questionnaire (EQ-5D-5L) and 12-question WHO Disability Assessment Schedule 2.0 (WHODAS 2.0) were answered for both groups. The univariate regression analysis was carried out using SPSS (v 20) and significance was established at 5%. RESULTS: The median duration between COVID-19 diagnosis in children and adolescents and longitudinal follow-up visits was 4.4 months (0.8-10.7). The median age of children and adolescents caregivers with laboratory-confirmed COVID-19 was similar to primary caregivers of subjects without laboratory-confirmed COVID-19 [43.2 (31.6-60.9) vs. 41.5 (21.6-54.8) years, p=0.08], as well as similar female sex (p=1.00), level of schooling (p=0.11), social assistance program (p=0.28), family income/month U (p=0.25) and the number of household’s members in the residence (p=0.68). The frequency of slight to extreme problems (level≥2) of the pain/discomfort domain according to EQ-5D-5L score was significantly higher in the former group [74% vs. 52.5%, p=0.03, OR=2.57 (1.14-5.96)]. The frequency of disability according to WHODAS 2.0 total score was similar to those without disability and unknown (p=0.79); however, with a very high disability in both groups (72.5% and 78.3%). Further analysis of primary caregivers of children and adolescents with post-COVID-19 condition (PCC) [n=12/51 (23%)] compared to those without PCC [n=39/51(77%)] revealed no differences between demographic data, EQ-5D-5L and WHODAS 2.0 scores in both groups (p>0.05). CONCLUSIONS: We longitudinally demonstrated that pain/discomfort were predominantly reported in approximately 75% of primary caregiver of COVID-19 patients, with high disability in approximately three-quarters of both caregiver groups. These data emphasized the prospective and systematic caregiver burden evaluation relevance of pediatric COVID-19.